Meritocracy, Integrity, and Local Wisdom in the Recruitment of Ad Hoc Supervisors: A Study of the Governance of the Sub-district Panwaslu Selection at the Bawaslu of Mesuji Regency - Ruyudha, Robby; Robi Cahyadi Kurniawan; Ence Sopyan (JURNAL TAPIS, 2026)
This article examines the recruitment of Subdistrict Election Supervisory Committee members in Mesuji Regency during the 2024 regional election. The study departs from the view that the quality of electoral oversight is not determined solely by legal design and institutional procedures, but also by the merit, integrity, and social legitimacy of ad hoc supervisors at the local level. This article aims to analyze the recruitment mechanism implemented by the Mesuji Regency Bawaslu, identify its organizational and bureaucratic challenges, examine the relevance of local wisdom in a multicultural society, and formulate a more substantive recruitment strategy. The study employs a qualitative descriptive approach with a case study design based on official recruitment documents, including recruitment reports, announcements, administrative forms, and the final list of selected candidates. The findings show that the recruitment process was procedurally orderly and administratively well documented, but remained highly formalistic. Candidate assessment relied mainly on administrative compliance, portfolios, and internal bureaucratic selection stages, while substantive aspects such as social reputation, public legitimacy, and contextual integrity were not yet fully incorporated. This article argues that recruitment should move beyond administrative formalism by integrating meritocracy, integrity verification, public participation, and sensitivity to local social conditions. It proposes a model of contextually integrated recruitment that combines formal administrative selection with limited, documented, and non-discriminatory social verification at the final stage